Comparative Study of Topical Steroids Vs Non steroidal Anti-Inflammatory Drugs to Control Post-Cataract Surgery Macular Edema: Doi: 10.36351/pjo.v40i1.1578 - Hafiz Muhammad Jahan Zaib; Nazir, Fahmina; Khan, Nida Armoghan; Khalid, Amina; Khan, Maha Izzat (Pakistan Journal of Ophthalmology, 2023)
Purpose: To compare the efficacy of topical steroids with non-steroidal anti-inflammatory drugs in controlling post-cataract surgery macular edema. Study Design: Quasi experimental study. Place and Duration of Study: “Pakistan Institute of Medical Sciences (PIMS), Islamabad, Pakistan” from 1st July 2022 to 31st December 2022. Methods: Forty patients who had undergone cataract surgery were selected for this study by convenient sampling. After informed consent, patients were divided into two groups: Group S (n = 20) was given 1% prednisone eye drops for 14 days while group N (n = 20) was given 0.1% nepafenac acid eye drops for 14 days. 30 days after surgery, central macular thickness (CMT), using OCT, was assessed and documented in both groups. Data was analyzed by SPSS 21. Results: Mean age of patients was 44.02 ± 6.08 years. There were 60% (24) males and 40% females. Mean pre-operative CMT difference between two groups was statistically insignificant. Post-operative CMT was significantly lower in group N as compared to group S [243.00 ± 21.71 µm vs 223.90 ± 17.52 µm; p = 0.004]. Frequency of post-operative ME was lower in group N as compared to group S [35% (7) vs 15% (3); p = 0.144]. Conclusion: Topical eye drops containing NSAIDs and steroids are useful to control post-cataract surgery macular edema but NSAIDs drops have better efficacy in controlling post-cataract surgery macular edema.